ACCULTURATION OF FOREIGN CULTURES IN THE SHORT STORY OF SERAMBI INDONESIA NEWSPAPER: AKULTURASI BUDAYA ASING DALAM CERPEN PADA SURAT KABAR SERAMBI INDONESIA - Ramli Ramli; Siti Aisha Nurhuda; Yusri Yusuf; Razali Razali; Siti Sarah Fitriani (Jurnal Kata, 2022)
This study aimed to describe the form of foreign cultures' acculturation in the short stories of Serambi Indonesia newspaper. The method used in this research is descriptive qualitative. The data collection was collected by conducting documentation techniques. To analyze the data, the researcher used content analysis with a literary anthropological approach. The data used were 12 short stories that were published in 2019. The results of the analysis show that the acculturation of foreign cultures from Hinduism, Buddhism, Arabic, and Europe is found in the Serambi Indonesia newspaper. Acculturation of foreign cultures originating from Hinduism and Buddhist is in the form of a culture of using ritual offerings and the takbiran parade by using a drum on the cultural elements of the religious system. Furthermore, the acculturation of Arab culture can be seen in the form of chanting poetry in art and the habit of wearing sarongs in living equipment systems. For the European cultural acculturation found in the form of the spread of brothels in the social system and the working culture as household assistants in the livelihood system.